Discontinuity of practices in environmental health: perception of municipal professionals in Southern Brazil (Sustainability in Debate, 2023)
This research investigates how professional knowledge could be employed as a conceptual strategy to understand the dismantlement of public policies regarding health and the environment. The goal was to examine the conditions and limitations perceived by health surveillance professionals involved directly with environmental issues and how that can affect their knowledge and professional practices. This research was based on a qualitative approach and an empirical nature, as it was performed through semi-structured interviews with an environmental health surveillance team linked to a public agency in a municipality in southern Brazil. Data analysis was performed by thematic coding and categorisation. The interviewees mentioned several recent performance difficulties linked to the concept of professional knowledge. Thus, the research concluded that the reduction in the number of professionals and other difficulties of environmental health teams represent negative impacts on the continuity of the work and preservation of the professional knowledge accumulated over the years.